Cell-free expression of NO synthase and P450 enzyme for the biosynthesis of an unnatural amino acid L-4-nitrotryptophan - Xintong Tian; Wan-Qiu Liu; Huiling Xu; Xiangyang Ji; Yushi Liu; Jian Li (Synthetic and Systems Biotechnology, 2022)
Cell-free system has emerged as a powerful platform with a wide range of in vitro applications and recently has contributed to express metabolic pathways for biosynthesis. Here we report in vitro construction of a native biosynthetic pathway for L-4-nitrotryptophan (L-4-nitro-Trp) synthesis using an Escherichia coli-based cell-free protein synthesis (CFPS) system. Naturally, a nitric oxide (NO) synthase (TxtD) and a cytochrome P450 enzyme (TxtE) are responsible for synthesizing L-4-nitro-Trp, which serves as one substrate for the biosynthesis of a nonribosomal peptide herbicide thaxtomin A. Recombinant coexpression of TxtD and TxtE in a heterologous host like E. coli for L-4-nitro-Trp production has not been achieved so far due to the poor or insoluble expression of TxtD. Using CFPS, TxtD and TxtE were successfully expressed in vitro, enabling the formation of L-4-nitro-Trp. After optimization, the cell-free system was able to synthesize approximately 360 μM L-4-nitro-Trp within 16 h. Overall, this work expands the application scope of CFPS for study and synthesis of nitro-containing compounds, which are important building blocks widely used in pharmaceuticals, agrochemicals, and industrial chemicals.